2018
DOI: 10.1016/j.jcin.2017.10.038
|View full text |Cite
|
Sign up to set email alerts
|

“Silent” Diabetes and Clinical Outcome After Treatment With Contemporary Drug-Eluting Stents

Abstract: Abnormal glucose metabolism was detected in 1 of 3 "nondiabetic" PCI patients and was independently associated with up to 4-fold higher event risks. Future intervention trials should determine whether meaningful benefits accrue from routine glycemia testing in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…encouraging patients to engage in local activities which can help them to improve their health problems and/or reducing their concerns about medication/chronic illness). Moreover, reinforcing positive patient beliefs in the need for medication is particularly important for "silent" chronic conditions, such as diabetes and HIV infection 24,25 . The use of good, targeted information to reduce patients' concerns about medications, and close supervision from the clinical team to promote patient selfmanagement, may be particularly beneficial in such conditions.…”
Section: Discussionmentioning
confidence: 99%
“…encouraging patients to engage in local activities which can help them to improve their health problems and/or reducing their concerns about medication/chronic illness). Moreover, reinforcing positive patient beliefs in the need for medication is particularly important for "silent" chronic conditions, such as diabetes and HIV infection 24,25 . The use of good, targeted information to reduce patients' concerns about medications, and close supervision from the clinical team to promote patient selfmanagement, may be particularly beneficial in such conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Of them, sixteen were further excluded because one of them was not a follow-up study, six did not include patients that underwent PCI, four did not report MACE outcome, four were without available outcome data, and the other one did not include controls with normoglycemia. Finally, twelve follow-up studies were included [12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…Forest plots for the meta-analysis of the incidence of MACE in patients with prediabetes compared to those with normoglycemia after PCI [12,15,16,18], retrospective cohort [13,14,17,18,20] or post-hoc analyses of the randomized controlled trials (RCTs) [21][22][23]. Two studies included patients with stable CAD [12,17], five studies included only patients with ST-segment elevation myocardial infarction (STEMI) [13,14,16,18,19], one with acute coronary syndrome (ACS) [23], while the other included a broad patients with CAD [20][21][22]. Primary PCI was applied in five studies [13,14,16,18,19], and elective PCI was applied in four studies [12,15,17,20].…”
Section: Study Characteristics and Quality Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports [20,21] also showed that the patency of the IRA in patients with STEMI was related to procedural success and decreased enzymatic infarct size, fatal arrhythmic events, and in-hospital mortality. Because recent studies [5][6][7] did not use TIMI ow grade as a variable in estimating the clinical outcomes between these two groups, we considered that the TIMI ow grade can be used as a meaningful variable for the comparison of major clinical outcomes between prediabetes and T2DM.…”
Section: Discussionmentioning
confidence: 99%